Hollow porous carbon spheres with hierarchical nanoarchitecture for application of the high performance supercapacitors. (1st September 2016) - Liu, Jia; Wang, Xianyou; Gao, Jiao; Zhang, Youwei; Lu, Qun; Liu, Min
Highlights: Hierarchical hollow porous carbon spheres are prepared by hydrothermal method. The HPCSs possess micro/mesoporous combination shell and macroporous core structure. The interconnected porous structure is modified by KOH activation. High specific capacitance of 303.9 F g −1 at 1 A g −1 is obtained for the AHPCSs. The AHPCSs show good cyclic property with capacitance 72.7 F g −1 after 5000 cycles. Abstract: Hollow porous carbon spheres (HPCSs) with micro/mesoporous combination shell and macroporous core are prepared through a facile and efficient hydrothermal method by using silica nanospheres as hard template and furfuryl alcohol (FA) as carbon source. Subsequently, the as-prepared HPCSs are further activated by KOH. The structure, morphology and electrochemical properties of carbon materials are characterized by scanning electron microscopy (SEM) and transmission electron microscopy (TEM), X-ray diffraction (XRD), Raman spectrum, Fourier infrared spectroscopy (FTIR), nitrogen adsorption/desorption isotherm, cyclic voltammetry (CV), galvanostatic charge/discharge tests (GCD), electrochemical impedance spectroscopy (EIS) and cycle life measurements. The results demonstrate that HPCSs possess unique well-balanced hierarchical porous structure with macropores, mesopores and micropores combination. Besides, HPCSs own easy-accessibly large surface area and high conductivity, which can result in ultrafast electrolyte ion transport and endow carbon materials outstanding capacitive performance, e.g. a high specific capacitance of 240.0 F g −1 for the HPCSs-2 electrode at current density of 1 A g −1 . Furthermore, the activated hollow porous carbon spheres (AHPCSs) exhibits a larger specific surface area of 1290 m 2  g −1 and a higher specific capacitance of 303.9 F g −1 at the same current density, indicating that AHPCSs are a promising electrode material for application of high performance supercapacitor.